2019
DOI: 10.4028/www.scientific.net/jbbbe.42.14
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Chitosan- Glycerol-HPMC Composite as Cornea Artificial Candidate

Abstract: The number of blindness is tend to be increased year by year. One of the blindness cause is cornea ulcer.The cause of cornea ulcer is bacteria, fungi, and herpes simplex virus. Cornea transplantation is the only treatment which could widely accepted for blindness. Transplant by donor network becomes the only treatment that is acceptable on a large for blindness. However, treatment donor transplants have many shortcomings in complications post surgery such as host response, donor limitations, incompatibility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Huh7it Heper Cells Show antibacterial properties. 2019 [150] Collagen-PCL corneal graft Human corneal epithelial cells Water absorption similar to native cornea. Facilitate cell adhesion, proliferation and migration.…”
Section: Corneal Epithelial Cellsmentioning
confidence: 99%
“…Huh7it Heper Cells Show antibacterial properties. 2019 [150] Collagen-PCL corneal graft Human corneal epithelial cells Water absorption similar to native cornea. Facilitate cell adhesion, proliferation and migration.…”
Section: Corneal Epithelial Cellsmentioning
confidence: 99%
“…Chitosan is biocompatible, biodegradable, inert and non-toxic 7 . Chitosan also have anti-fungal, anti-bacterial, and hemostatic properties so it is suitable for use as a material for tissue engineering 29 . Sodium hyaluronate is a glycosaminoglycan in the extracellular matrix, which has a vital role in wound healing and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In the eye plane, sodium hyaluronate has viscoelastic properties, so it is often used to protect the corneal endothelium and maintain the anterior chamber's depth during cataract surgery. Animal studies have also shown that sodium hyaluronate supports corneal epithelial wound healing by stimulating corneal epithelial migration, adhesion, and proliferation 8 .The addition of chitosan to collagen can improve its stability and structural integrity so that it can be implanted in the eye 9 and the addition of sodium hyaluronate improves light transmission 28,29 . This study attempted to evaluate the differences in Collagen-Chitosan-sodium hyaluronates (Col-Chi-NaHa) intrastromal implantation to the corneal haziness level TGF-ß expression in stromal injury on New Zealand rabbits eye.…”
Section: Introductionmentioning
confidence: 99%